Furio Jesi: Myth and Biography - Ruvituso, Mercedes (Escritura e Imagen, 2024)
When, in 1972, Furio Jesi first elaborated his model of the “mythological machine”, hestarted from a particular reading of the “myth of Rimbaud” and his legendary participation in the ParisCommune. However, in the context of May 1968, he also aims to question his own present: why domythical epiphanies in the revolts of yesterday and today end in a “religio mortis”? This paper aims to“dismantle” the first formulation of the “mythological machine” in order to locate conceptually howit is constructed on the basis of the aporia between myth and “biography”. On the one hand, it will beshown that, in parallel to Guy Debord’s situationism, Jesi takes up, not always explicitly, certain placescommon to Walter Benjamin’s task of demythologisation: childhood, the commodity, revolt. On theother hand, the conceptual tension between myth and biography that redefines the distinction betweenbios and zoé will be interpreted as an equally “biographical” response to Karl Kerényi.
Keywords: Rimbaud; mythological machine; revolt; Benjamin; Kerényi